Improving of safety in transport by means of telematic systems - Borošová, Dana (Doprava a spoje, 2006)
Improving of safety and safety parameters in transport as well as a gradual introduction of safety rules are becoming one of the most important components in the evaluation of thequality of transport. Ensuring of safety must be supported by the legislative and econotools in accord with the EU procedures.